Social security (EsSalud) in Peru, ¿dissonance in the system? - Bardales-Zuta , Víctor Hugo (2023)
The Social Security of Health (EsSalud), in Peru; is an organization attached to the Ministry of Labor and Employment Promotion, it is within the scope of the National Fund for Financing State Business Activity (FONAFE), linked to the Ministry of Economy and Finance (MEF). It was created in the 1990s, replacing the Peruvian Institute of Social Security (IPSS) through Law No. 27056 creating Social Security for Health. We consider five aspects in the probable dissonance of EsSalud with the system, the first the legal conception, second the infrastructure, third the processes, fourth the human resources and fifth the role of the state.